Impulsive buying behavior: scarcity impact of flash sale through arousal as mediating variable - Nilam Fathia; Amelindha Vania (Institute of Computer Science (IOCS), 2023)
The scarcity of flash sales is one of the causes of the tendency of individuals to make higher impulse purchases. This study sought to investigate the direct connection between flash sales and impulsive purchases through arousal as a mediator among 160 Generation Z in South Kalimantan who had shopped for flash sales at e-commerce Shopee. This study used an explanatory approach with 160 respondents. The data analysis method makes use of SmartPLS 4.0's Partial Least Square-Structural Equation Modeling (PLS-SEM). This study reveals that limited quantity scarcity and arousal positively and significantly affect impulsive buying. In contrast, limited time scarcity has a positive but insignificant effect on impulsive buying. In addition, the study results show that limited quantity scarcity and limited time scarcity have a positive and significant impact on arousal. In contrast, limited quantity scarcity and limited time scarcity have an indirect effect on impulsive buying through arousal. The research provides managerial implications for business owners to focus on the scarcity of flash sales to create an arousal stimulus for consumers, which results in impulse buying. This research is expected to provide knowledge to business owners regarding product marketing strategies at Shopee that are used to support increased sales